2014
DOI: 10.1504/ijism.2014.064356
|View full text |Cite
|
Sign up to set email alerts
|

Reverse food logistics during the product life cycle

Abstract: This study aimed to examine reverse logistics across the food product life cycle. The literature review of reverse logistics factors in food industry produced a set of supply chain performance measures. Using a survey, questionnaires were sent to 200 practitioners with experience in food supply chain operations. In total, 48 usable questionnaires were returned, resulting in 24% response rate. The contribution of this study lies in extending the body of knowledge of reverse food logistics during product life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…RL is necessary in the food industry to provide high‐quality and safe food to consumers without any damage to human life and the environment (Vlachos, 2014). RL in the food industry deals with a range of challenges such as food returns, food recalls, recycling, reuse, and disposal (Vijayan, Kamarulzaman, Mohamed, & Abdullah, 2014).…”
Section: Reverse Logistics In Food Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…RL is necessary in the food industry to provide high‐quality and safe food to consumers without any damage to human life and the environment (Vlachos, 2014). RL in the food industry deals with a range of challenges such as food returns, food recalls, recycling, reuse, and disposal (Vijayan, Kamarulzaman, Mohamed, & Abdullah, 2014).…”
Section: Reverse Logistics In Food Supply Chainsmentioning
confidence: 99%
“…The food industry is a very suitable field for recycling in a circular economy (Heydari, Govindan, & Sadeghi, 2018). RL activities are necessary to ensure high quality and food safety due to rapid damage and short shelf life (Vlachos, 2014). In addition, the food supply chain is more complex due to its short shelf life (Khalafi, Hafezalkotob, Mohamaditabar, & Sayadi, 2020; Noya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The aspiration for bioeconomic transition gives rise to different logistical challenges than those seen in traditional forward logistics and requires design of customised supply chains and logistics solutions for key activities such as material forecasting and handling, storage, transport, packaging, transparency and traceability. (Romsdal 2014, Vlachos, 2014, Grant et al 2013.…”
Section: 2mentioning
confidence: 99%
“…Peer and industry conformity allows companies to meet the expectations of purchasers, users, government, producers and suppliers regarding matters such as quality, safety, price, performance, and sustainability. For example, upstream suppliers' raw materials defects or errors in design, production, and assembling may directly generate great influence on the reverse logistics of downstream enterprises or even the entire supply chain (Vlachos 2014;Polák and Drápalová 2012). Scharnhorst et al (2006) conducted a Life Cycle Assessment (LCA) of mobile phones and found that recycling the electronic scrap of mobile phone networks have clear environmental benefits.…”
Section: Transaction Cost Economicsmentioning
confidence: 99%